(untitled) (Ágora Journal, 2022)
The article addresses the racial issue as an expression of the social issue, having the 19th century as the confluence of racialist theories and the origin of inequality in access to land with the law’s land of 1850, among other mechanisms created by the State to maintain white European domination in these lands. Based on the notion of the settlement of indigenous and black resistance, it makes use of the articulation between race and class, based on classic and contemporary authors of the Brazilian social formation, to read the current reality of human rights violations in Brazil. The understanding of the colonial process and enslavement are approached from Marx’s reading of the primitive accumulation of capital that maintains violence and expropriation over 522 years as a basis for the maintenance of capitalist exploitation and is updated in this moment of structural crisis of the capital with the advance on indigenous lands in the so-called time frame, on quilombola lands and the maintenance of state violence against the black population in the slums and outskirts of citie for the expropriation of urban land, extermination and incarceration of the black and indigenous population in an urban context.